Analisis Kemampuan Berpikir Kritis Siswa dalam Memecahkan Masalah pada Kelas IV Sekolah Dasar. - Ayunda Fitri Milenia; Mu’jizatin Fadiana; Heny Sulistyaningrum (STKIP Subang, 2026)
Critical thinking is an important skill that needs to be developed from elementary school. This study aims to analyze the critical thinking skills of fourth-grade students in solving problems on the topic